The Shifting Salience of Skin Color for Educational Attainment. (December 2019) - Branigan, Amelia R.; Freese, Jeremy; Sidney, Stephen; Kiefe, Catarina I.
Findings of an association between skin color and educational attainment have been fairly consistent among Americans born before the civil rights era, but little is known regarding the persistence of this relationship in later born cohorts. The authors ask whether the association between skin color and educational attainment has changed between black American baby boomers and millennials. The authors observe a large and statistically significant decline in the association between skin color and educational attainment between baby boomer and millennial black women, whereas the decline in this association between the two cohorts of black men is smaller and nonsignificant. Compared with baby boomers, a greater percentage of the association between skin color and educational attainment among black millennials appears to reflect educational disparities in previous generations. These results emphasize the need to conceptualize colorism as an intersectional problem and suggest caution when generalizing evidence of colorism in earlier cohorts to young adults today.